Bell casting using gema’s local clay: Mold performance and gating design influence variations - Dedy Masnur (BKS-TM Indonesia, 2025)
Indonesia has a large potential of natural clays, one of which is located in Gema Village, Lipat Kain Subdistrict, Kampar Regency, Riau Province. This study aims to examine the use of Gema clay as a molding material and gating system design for bell making through a number of defects, dimensional accuracy, and hardness values. The molds were designed with a sprue; two sprues; and a sprue and a riser. The Gema village clay was formed into two mold halves, the lower and upper molds. Then, the molds were dried and sintered at 359 °C. Al-4.5wt.%Cu was melted in a crucible furnace to 780 °C, then poured into the mold. The defects were observed, the representative of dimensions and the hardness were measured. The results show there are two types of defects that were observed as a result of the use of clay and channel system: incomplete casting and pin holes. The a sprue and a riser design has a lowest percentage error of 0.35% and a hardness of 56.486 VHN.